Biaxial extensional viscosity in wheat flour dough during baking. (November 2018) - Vanin, F.M.; Lucas, T.; Trystram, G.; Michon, C.
Abstract: Lubricated squeezing flow (LSF) experiments on wheat flour dough were conducted at a constant biaxial extensional rate followed by relaxation experiments. The effect of temperature on the rheology of the dough was studied in the range 25–95 °C under small and large strain to characterize changes in the dough through a possible pathway to simulate the dough-crumb transition during the first step of the baking process. A strain hardening effect was shown over the whole temperature range. Like extensional viscosity measured at 0.1 and 0.65 biaxial strain, the consistency index ( K ) decreased from 25 °C to 45 °C and increased at temperatures above 50 °C. Two levels of the behaviour index ( n ) were found: 0.35–0.40 below 45 °C, and 0.1–0.2 above 45 °C. The relaxation degree also changed dramatically but only at higher temperatures (56–60 °C), below which it remained almost constant (98-99%), once the dough became a viscoelastic liquid, above this temperature the main physical-chemical reactions (starch and protein) started to occur, leading to more solid properties. These results complement those of LSF. LSF experiments at large biaxial strain (0.75), combined with a relaxation experiment, were successfully used for dough/crumb characterisation at a temperatures ranging from 25 °C to 74 °C. Alpha values estimated from Launay's model were incorporated in the flow behaviour index, underwent the same type of changes as a function of temperature as n but with a less marked transition; n was divided by two and K increased by about one decade. Highlights: Physico chemical properties of wheat flour doughs evolve greatly with temperature. The first step of baking could be model using a rheometer. Wheat flour dough rheological properties were characterized in a larger gap conditions. Gluten thermosetting and starch gelatinisation contributions are followed.